Optimality in a World of Progress and Learning - Zeckhauser, Richard (Review of Economic Studies, 1968)
Journal Article Optimality in a World of Progress and Learning Get access Richard Zeckhauser Richard Zeckhauser London School of Economics, Visitor, Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 3, July 1968, Pages 363–365, https://doi.org/10.2307/2296671 Published: 01 July 1968